(untitled) (International Journal of Environmental Sciences, 2025)
The construction sector in China has had to deal with problems with project delivery that have caused delays, budget overruns, and quality issues. Many people use Building Information Modeling (BIM) as a digital innovation tool, but it hasn’t always reached its full potential since it doesn’t work well with project management tools in organizations. This study came up with and tested an Integrated BIM and Project Management Maturity (PMM) Framework to help construction projects do better. The study used a mixed-methods approach, which included qualitative case studies and interviews as well as a quantitative survey of 200 professionals in the Chinese construction industry. The results showed a substantial positive relationship between BIM maturity, PMM levels, and important performance factors like time, cost, and quality. A multiple regression study showed that both BIM and PMM had a big effect on project outcomes, making for 62% of the difference in overall performance. Experts checked the framework again, and a pilot project on a public infrastructure project proved it worked. The study found that strategically combining BIM and PMM can help China’s changing construction industry reach its highest level of performance.